Matrix association region/scaffold attachment region (MAR/SAR) sequence: its vital role in mediating chromosome rearrangements in nasopharyngeal carcinoma via oxidative stress-induced apoptosis. - Tan, Sang Nee; Sim, Sai Peng; Alan S., B. Khoo (Biomed Central, 2018)
Background: Oxidative stress is known to be involved in most of the aetiological factors of nasopharyngeal car‑ cinoma (NPC). Cells that are under oxidative stress may undergo apoptosis. We have previously demonstrated that oxidative stress-induced apoptosis could be a potential mechanism mediating chromosome breakages in naso‑ pharyngeal epithelial cells. Additionally, caspase-activated DNase (CAD) may be the vital player in mediating the chro‑ mosomal breakages during oxidative stress-induced apoptosis. Chromosomal breakage occurs during apoptosis and chromosome rearrangement. Chromosomal breakages tend to cluster in certain regions, such as matrix association region/scafold attachment region (MAR/SAR). We hypothesised that oxidative stress-induced apoptosis may result in chromosome breaks preferentially at the MAR/SAR sites. The AF9 gene at 9p22 was targeted in this study because 9p22 is a deletion site commonly found in NPC. Results: By using MAR/SAR recognition signature (MRS), potential MAR/SAR sites were predicted in the AF9 gene. The predicted MAR/SAR sites precisely match to the experimentally determined MAR/SARs. Hydrogen peroxide (H2O2) was used to induce apoptosis in normal nasopharyngeal epithelial cells (NP69) and NPC cells (HK1). Nested inverse polymerase chain reaction was employed to identify the AF9 gene cleavages. In the SAR region, the gene cleavage frequency of H2O2-treated cells was signifcantly higher than that of the non-treated cells. A few chromosomal break‑ ages were detected within the AF9 region which was previously found to be involved in the mixed lineage leukae‑ mia (MLL)-AF9 translocation in an acute lymphoblastic leukaemia patient. As for the non-SAR region, no signifcant diference in the gene cleavage frequency was found between the untreated control and H2O2-treated cells. Further‑ more, H2O2-induced cleavages within the SAR region were reduced by caspase-3 inhibitor, which indirectly inhibits CAD. Conclusions: These results reafrm our previous fndings that oxidative stress-induced apoptosis could be one of the potential mechanisms underlying chromosome breakages in nasopharyngeal epithelial cells. MAR/SAR may play a vital role in defning the location of chromosomal breakages mediated by oxidative stress-induced apoptosis, where CAD is the major nuclease